Barriers to construction industry stakeholders’ engagement with sustainability: toward a shared knowledge experience - Wilson, Ian E.; Rezgui, Yacine (Technological and Economic Development of Economy, 2013)
Sustainability ill-practices in the construction industry can have major drawbacks on meeting governmental targets on carbon and energy reduction. Using a mixed-method approach drawn from three studies to explore the level of engagement of construction stakeholders in adopting government sustainability agendas, the research identifies a wide range of perceived barriers, which operate broadly at ‘individual’ and ‘organisational’ levels. Sustainability knowledge in construction is fragmented, diverse, embedded in various documents, and developed in a non-concerted and integrated way across stakeholders, localities, regions, and countries. There is an emergent need for a socio-technical ‘knowledge solution’ to create circles of impacts that bind building professionals, energy administrations, and citizens in a shared sustainability experience to address a number of issues.